Memento Mori: Can art assist student nurses to explore death and dying? A qualitative study. (June 2020) - Nicol, Jane; Pocock, Mary
Abstract: Objective: To report how an art-based workshop assisted undergraduate nursing students to explore their experiences and beliefs about death and dying. Design: A descriptive qualitative study. Participants: Year three adult nursing students studying on a full-time undergraduate pre-registration programme. Methods: Long answer questionnaires were completed by 48 undergraduate student nurses, all of whom had participated in the art-based workshop. Qualitative thematic analysis was used to identify, analyse and report themes identified. Results: Four themes were identified: (1) exploring experiences and beliefs, (2) the role of the art in supporting discussions, (3) the gallery environment, and (4) impact on practice. Participants valued the opportunity to 'slow down', fully examine, and be challenged by, the art prompting reflective and critical discussion. The calm and peaceful gallery environment, and the skilled facilitation increased participant confidence to share experiences and beliefs. Reflecting on the workshop participants reported the workshop increased their understanding of the complexities of care and of addressing these on an individual basis. Conclusions: This shared experience encouraged open and honest discussion and reflection, enhanced critical thinking and the need for compassionate person, and family-centred palliative and end-of-life care. While this study focused on an educational strategy delivered to student nurses, it is an approach that could be used with other health and social care professionals. Close and critical observation of the selected art increased participant understanding and insight of the many experiences and interpretations of death and dying.